Huge gallstone complicating laparoscopic cholecystectomy - Banigo, Adonye (BMJ Publishing Group, 2013)
Gallstone disease is common in the western world and is most often diagnosed on ultrasound scanning. This case is of a 57-year-old woman with a history of biliary colic who was admitted as a day case for a laparoscopic cholecystectomy. This was converted to open because of the technical difficulty related to a huge gallstone in the gallbladder measuring 60 mm×30 mm×35 mm, the largest we have seen. Review of her ultrasound scan showed this large stone present at the time. Several factors are known to increase the risk of conversion to open, and these patients require a longer in-hospital stay postoperatively. Prior knowledge of these factors may advocate preoperative admission to a unit with inpatient beds available, not a day case unit. This will help save costs involved in ambulance transfers of day case patients to inpatient units and support the efficient use of our elective and emergency services.